Dechlorination performance in chemical looping conversion of polyvinyl chloride plastic waste using K/Na/Ca-modified iron ore oxygen carriers. Issue 2 (April 2022) - Jiang, Hongming; Huo, Ruiqiang; Zhang, Zhen; Lin, Yan; Zhao, Zengli; Hu, Jianjun; Huang, Zhen; Huang, Hongyu; Li, Haibin
Abstract: The reducing atmosphere of chemical looping conversion (CL) can greatly limit the emission of polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs) during the heat treatment of polyvinyl chloride plastics waste (PPW). Loading alkali metals and alkaline earth metals (AAEM) on iron ore OC can remove chlorine in situ, reduce HCl corrosion, and further reduce the emission of other harmful chlorine pollutants. In this work, iron ore OC was modified by K, Na, and Ca. The three modified OCs showed good dechlorination and catalytic gasification performances, while the pristine iron ore OC only exhibited weak dechlorination effects. The dechlorination activity of the three OCs was found to decrease in the order K- > Na- > Ca-modified OC. Decreasing the reaction temperature in the range of 750–900 °C and increasing the dechlorination agent loading improved the dechlorination efficiency. The AAEM conversion of K- and Na-modified OCs could reach or approach 100%, while that of Ca-modified OC reached only about 30%. Scanning electron microscopy with energy-dispersive spectroscopy (SEM-EDS) and X-ray diffraction (XRD) results showed that the corresponding alkali and alkaline earth metal chlorides were formed on the surface of the OCs during the CL processes. Graphical Abstract: ga1 Highlights: The K/Na/Ca modified OC is thermodynamic beneficial to the removal of HCl. The dechlorination performance of K/Na/Ca modified iron ore OCs were studied. The modification of K/Na/Ca improve the OC reactivity and HCl removal. High temperature inhibits dechlorination. 15% K loaded OC showed the highest dechlorination efficiency of 98.71%.